Effectiveness of ozonation with zirconium and tin tetrachloride for stabilized anaerobic landfill leachate treatment - Siti Nor Farhana Zakaria; Hamidi Abdul Aziz; Motasem Y. D. Alazaiza (John Wiley & Sons, Inc, 2021)
Landfill leachate can threaten the environment and human life. Therefore, this study aims to investigate the efficiency of ozone (O3), O3 with zirconium tetrachloride (O3/ZrCl4), and O3 with tin tetrachloride (O3/SnCl4) in remediating the stabilized anaerobic landfill leachate (SAL) from Alor Pongsu, Perak. Hydroxyl radical (OH•) is an important oxidizing agent in the ozonation process. Its presence was tested using tert-butyl alcohol. Results showed that using ZrCl4 and SnCl4 in ozonation boosted the generation of hydroxyl radical, thereby enhancing the oxidation process and pollutant removal inside the sample. The O3/ZrCl4 mix at chemical oxygen demand (COD) to ZrCl4 ratio of 1:1.5, pH 8–9, and 90-min reaction time resulted in the highest reduction rates of COD and color at 91.9% and 99.6%, respectively. All results demonstrated that the optimum performance occurred at alkaline conditions (pH > 8), proving that OH radicals primarily oxidized the pollutants through an indirect reaction pathway. The biodegradability (biochemical oxygen demand/COD) ratio was also considerably improved from 0.02 (raw) to 0.37 using O3/ZrCl4, compared with using O3 alone and using O3/SnCl4, which only recorded 0.23 and 0.28, respectively, after the treatment. The study demonstrated that O3/ZrCl4 was the most efficient combination.